Do non-crop areas and landscape structure influence dispersal and population densities of male olive moth? - Villa, Maria (2020)
The permeability of the crop surroundings to pests and the landscape structure can influence pest dispersal between crop patches as well as its abundance within the crop. In this work, we analyzed the dispersal of the olive moth Prays oleae (Bernard) throughout the olive grove surroundings and their abundance within the crop following three approaches: (i) pollen grains settled on bodies of olive moths collected in olive groves were identified and compared with flora occurring on the surrounding patches; (ii) the capability of P. oleae males to penetrate non-crop patches was analyzed (iii) the effect of the landscape structure on the abundance of the three generations of the olive moth was studied. Pollen grains of scrubs and other trees occurring in the crop surroundings, such as Cistus sp., Quercus sp., Juniperus-type or Pinaceae were identified on P. oleae bodies suggesting that P. oleae penetrates into non-crop habitats. Additionally, woody and, to a lesser degree, herbaceous patches, did not constitute barriers for P. oleae. Finally, more complex and heterogeneous patches presented lower numbers of captures of P. oleae. These results give new insights into the movements of the olive moth in the olive grove surroundings and suggest that the management of non-crop areas could influence this pest abundance.